Bridging the Gap: Exploring the Preclinical Potential of Pereskia grandifolia in Metabolic‐Associated Fatty Liver Disease - Albuquerque, Edilson Rodrigues; da Silva, Gustavo Ratti; de Abreu Braga, Fernanda; Silva, Ester Pelegrini; Negrini, Karina Sposito; Fracasso, Julia Amanda Rodrigues [UNESP]; Guarnier, Lucas Pires; Jacomassi, Ezilda; Ribeiro-Paes, João Tadeu [UNESP]; da Silva Gomes, Roberto; Gasparotto, Arquimedes; dos Reis Lívero, Francislaine Aparecida (Wiley, 2023)
Metabolic-associated fatty liver disease (MAFLD) is a complex condition characterized by steatosis and metabolic disturbances. Risk factors such as diabetes, cigarette smoking, and dyslipidaemia contribute to its development and progression. Effective and safe therapies for MAFLD are urgently needed. Pereskia grandifolia has shown potential as an alternative treatment, but its effectiveness against liver disease remains unexplored. This research aims to determine the hepatoprotective properties of P. grandifolia using a model of MAFLD. The study was carried out through various phases to assess the safety and efficacy of the ethanol-soluble fraction of P. grandifolia. Initially, an in vitro assay was performed to assess cell viability. This was followed by an acute toxicity test conducted in rats to determine the safety profile of the extract. Subsequently, the anti-inflammatory properties of P. grandifolia were examined in macrophages. For the MAFLD study, diabetic Wistar rats were made diabetic and exposed to a high fat diet and cigarette smoke, for 4 weeks. During the last 2 weeks, the rats were orally given either the vehicle (negative control group; C-), P. grandifolia (30, 100, and 300 mg/kg), or insulin in addition to simvastatin. A basal group of rats not exposed to these risk factors was also assessed. Blood samples were collected to measure cholesterol, triglycerides, glucose, ALT, and AST levels. Liver was assessed for lipid and oxidative markers, and liver histopathology was examined. P. grandifolia showed no signs of toxicity. It demonstrated anti-inflammatory effects by inhibiting phagocytosis and macrophage spreading. The MAFLD model induced liver abnormalities, including increased AST, ALT, disrupted lipid profile, oxidative stress, and significant hepatic damage. However, P. grandifolia effectively reversed these changes, highlighting its potential as a therapeutic agent. These findings emphasize the significance of P. grandifolia in mitigating hepatic consequences associated with various risk factors.